T-cell activation by the CD28 ligand B7 is required for cardiac allograft rejection in vivo. - Turka, L A (1992)
Organ graft rejection is a T-cell-dependent process. The activation of alloreactive T cells requires stimulation of the T-cell receptor/CD3 complex by foreign major histocompatibility complex (MHC)-encoded gene products. However, accumulating evidence suggests that, in addition to T-cell receptor occupancy, other costimulatory signals are required to induce T-cell activation. Previously, the CD28 receptor expressed on T cells has been shown to serve as a surface component of a signal transduction pathway that can provide costimulation. In vitro, interaction of CD28 with its natural ligand B7 expressed on the surface of activated B cells or macrophages can act as a costimulus to induce proliferation and lymphokine production in antigen receptor-activated T cells. We now report evidence that stimulation of T cells by the CD28 ligand B7 is a required costimulatory event for the rejection of a MHC-incompatible cardiac allograft in vivo. These results demonstrate that the B7/CD28 activation pathway plays an important role in regulating in vivo T-cell responses.